Epidemiological and Genomic Landscape of Azole Resistance Mechanisms in Aspergillus Fungi - Hagiwara, Daisuke; Watanabe, Akira; Kamei, Katsuhiko; Goldman, Gustavo H. (Frontiers in Microbiology, 2016)
Invasive aspergillosis is a life-threatening mycosis caused by the pathogenic fungus Aspergillus. The predominant causal species is Aspergillus fumigatus, and azole drugs are the treatment of choice. Azole drugs approved for clinical use include itraconazole, voriconazole, posaconazole, and the recently added isavuconazole. However, epidemiological research has indicated that the prevalence of azole-resistant A. fumigatus isolates has increased significantly over the last decade. What is worse is that azole-resistant strains are likely to have emerged not only in response to long-term drug treatment but also because of exposure to azole fungicides in the environment. Resistance mechanisms include amino acid substitutions in the target Cyp51A protein, tandem repeat sequence insertions at the cyp51A promoter, and overexpression of the ABC transporter Cdr1B. Environmental azole-resistant strains harboring the association of a tandem repeat sequence and punctual mutation of the Cyp51A gene (TR34/L98H and TR46/Y121F/T289A) have become widely disseminated across the world within a short time period. The epidemiological data also suggests that the number of Aspergillus spp. other than A. fumigatus isolated has risen. Some non-fumigatus species intrinsically show low susceptibility to azole drugs, imposing the need for accurate identification and drug susceptibility testing in most clinical cases. Currently, our knowledge of azole resistance mechanisms in non-fumigatus Aspergillus species such as A. flavus, A. niger, A. tubingensis, A. terreus, A. fischeri, A. lentulus, A. udagawae, and A. calidoustus is limited. In this review, we present recent advances in our understanding of azole resistance mechanisms particularly in A. fumigatus. We then provide an overview of the genome sequences of non-fumigatus species, focusing on the proteins related to azole resistance mechanisms.